Pengaruh Ekstrak Etanol Pegagan (Centella asiatica ) Terhadap Volume Hippocampus Tikus (Rattus norvegicus) Pasca Stres Kronik - Zulhamidah, Yenni; Wiyono, Nanang; Ratna Sari, Dwi Cahyani; Partadiredja, Ginus (Lembaga Penelitian Universitas YARSI, 2013)
Background. Chronic stress caused by restraint stress induces an increase in corticosterone (glucocorticoid) that result decreased hippocampal vollume. Centella asiatica has long been used for various neurological disturbances in Southeast Asian countries. Aims. The research aims to investigate the effects of ethanol extracts of Centella Asiatica to prevent the decrease of hippocampal vollume after chronic stress. Methods. Thirty male adult rats (Sprague Dawley) with body weight of 250-350 gram was randomly subdivided into six groups of treatments: Nonstress control group was given 2% Pulvis Gummi Arabicum (PGA), Stress control groups( PGA 2 %), groups treated with fluoxetine 10mg/kgbw/day , and Ca150, Ca300, Ca600 containing ethanol extracts of Centella asiatica with doses 150 mg/kgbw/day, 300 mg/kgbw/day, 600 mg/kgbw/day a, respectively followed by restraint stress. After 21 days of stress, rats underwent Morris Water Maze test for 6 days, perfused, and hippocampus was collected for histological processing. Toluidine blue staining is used to asses the estimation of hippocampal volume. Results. The estimated hippocampal volume were 3.1512 ± 1.01 (nonstress), 2.4736 ± 0.10 (stress), 2.7018 ± 1.06 (Ca150), 2.7405 ± 1.19 (Ca300), 2.2678 ± 0.82 (Ca600) and 2.5818 ± 0.70 (Fluoxetine). Statistic test showed that there were no significant diferrence between stress control group and groups treated. Conclusion. There is no the significant effects of Ethanol extracts of Centella Asiatica to prevent the decrease of hippocampal vollume after chronic stress.